Suspected Metal Allergy and Femoral Loosening After Total Knee Arthroplasty: A Diagnostic Dilemma - Elizabeth G. Lieberman, MD; Robert L. Barrack, MD; Thomas P. Schmalzried, MD (Arthroplasty Today, 2021)
Metal sensitivity is increasingly prevalent and is associated with negative outcomes after total knee arthroplasty (TKA). Currently, there is no consensus on diagnostic criteria for TKA failure from immune reaction. We present a patient who had pain and aseptic effusion 2 years after TKA. Radiographs were concerning femoral loosening. Lymphocyte transformation testing showed nickel sensitivity. During revision surgery, the femoral component was loose. The histologic aseptic lymphocyte-dominated vasculitis-associated lesion score was 4 with elevated CD4+ lymphocytes, consistent with sensitization. Nickel-free revision implants were used. One year after surgery, the patient is symptom-free. This case has features suggestive of an immune reaction, with femoral loosening, and is illustrative of the diagnostic dilemma. Using a hypoallergenic knee eliminates future concern for nickel sensitivity.